Global diversity of marine fishes caught in bottom trawl fisheries - Sarah J. Foster; Syd J. Ascione; Isak B. Boyd; Amanda C. J. Vincent (Reviews in Fish Biology and Fisheries, 2026)

Nutrition Services in Oncology: A Cross-Sectional Survey of Patient Experiences, Needs, and Gaps in Care - Bailey M. Foster; Melissa F. Miller; Colleen K. Spees; Cynthia A. Thomson; Elaine B. Trujillo; Erica E. Fortune; Lauren Fay; Peter A. Adintori; Renee Stubbins; Jill M. Hamilton-Reeves (Journal of the Academy of Nutrition and Dietetics, 2026)

Caldera faults can be sintered volcanic conduits without necessarily requiring catastrophic rapid slip events - Frankie L. Haywood; Fabian B. Wadsworth; Madeleine C.S. Humphreys; Dave McGarvie; Richard J. Brown; Alexander A. Iveson; Leon Bowen; Annabelle Foster (Earth and Planetary Science Letters, 2026)

Correction: The influence of mouth pressure on the cardiovascular response during inspiratory muscle loading at a constant transdiaphragmatic pressure - Megan L. Lance; Scott F. Thrall; Benjamin P. Thompson; Leah M. Mann; Jou-Chung Chang; Katherine M. Taylor; Nadia M. Navarro Solano; Madison J. Gorsline; Richard J. A. Wilson; Trevor A. Day; Paolo B. Dominelli; Glen E. Foster (European Journal of Applied Physiology, 2026)

Eight recommendations to enhance biodiversity outcomes of nature-based solutions at multiple scales - Charles B. van Rees; Collin VanBuren; Lori A. Han; Andrew Altieri; Matt Bilskie; James E. Byers; Jon Calabria; Matthew L. Chambers; Daniel J. Coleman; Katie Foster; Aliza Leit; Alec Nelson; et al. (Journal of Environmental Management, 2026)

Laboratory-grown crust in planktic foraminifera Neogloboquadrina pachyderma; insights into resolving inaccuracies in polar palaeotemperature estimates - Adele Westgård; Mohamed M. Ezat; Freya E. Sykes; Gavin L. Foster; Julie Meilland; Thomas B. Chalk; J. Andy Milton (Geochimica et Cosmochimica Acta, 2026)

Dietary nitrate supplementation does not improve resistance exercise performance in resistance-trained women - Sydney N. Brennan; Justin M. Foster; Raymond T. Gerardo; Trevor J. Molnar; Ryan Tran; Christopher B. Sottile; Kyle S. Geppert; Michael Egiazarian; Abigail F. Ballhagen; Money Ghimire; John R. M. Renwick; Lewis A. Gough; et al. (European Journal of Applied Physiology, 2026)

Climate Predicts Tree Dispersal Strategies Across Brazil's Ecosystems - Fernanda C. Souza; Vinícius Andrade Maia; Renata Françoso; Matheus Coutinho Freitas de Oliveira; Ana Beatriz Ligo; Bruno X. Pinho; Jesús Aguirre‐Gutiérrez; Martin Sullivan; Larissa Rocha‐Santos; Laura de Brito Évora; Leonardo de Sousa Miranda; María Natalia Umaña; et al. (Global Ecology and Biogeography, 2026)
Aim We investigate the distribution of dispersal modes — endozoochory (via animal ingestion), synzoochory (via animal seed accumulation) and anemochory (via wind)—and seed mass of woody plants across Brazilian ecosystems, testing whether their relative abundance in local plant communities could be predicted by climate, edaphic factors and dispersal agents (e.g., the main vectors moving seeds). We expected climate to be the main predictor of dispersal strategy abundance. Location Brazilian ecosystems (Amazon, Atlantic Forest, Cerrado and Caatinga). Time Period 2004–2020. Major Taxa Studied Woody angiosperms, trees and shrubs. Methods We assigned seed mass to 1984 species and dispersal mode to 2203 species within 300 old‐growth and non‐flooded plots. We employed Random Forest regressions to assess the influence of water availability, temperature seasonality, soil fertility, wind and frugivorous primates on the community‐weighted means of seed mass and dispersal modes. We mapped predictions and estimated the area of applicability to identify regions where predictions were reliable. Results Climate was the main factor predicting tree dispersal strategies, followed by dispersal agents or soil properties. Endozoochory was prevalent in wetter regions with high water availability and greater diurnal temperature range. Anemochory was more common in drier regions with low water availability, stronger winds and greater diurnal temperature range, whereas synzoochory was more abundant in areas with low temperature seasonality. Heavier seeds were more prevalent in regions with less seasonal temperatures, smaller diurnal temperature ranges and weaker winds. Main Conclusions Climate is a key predictor of the distribution and prevalence of plants with contrasting dispersal modes and seed masses. We thus expect functional responses to environmental change associated with shifts in the relative abundance of dispersal strategies, with implications for ecosystem services. Our results also highlight the critical role of plot‐based datasets in improving our understanding of how environmental factors influence seed dispersal strategies across tropical ecosystems.

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

The influence of mouth pressure on the cardiovascular response during inspiratory muscle loading at a constant transdiaphragmatic pressure - Megan L. Lance; Scott F. Thrall; Benjamin P. Thompson; Leah M. Mann; Jou-Chung Chang; Katherine M. Taylor; Nadia M. Navarro Solano; Madison J. Gorsline; Richard J. A. Wilson; Trevor A. Day; Paolo B. Dominelli; Glen E. Foster (European Journal of Applied Physiology, 2026)

Individual foraminiferal analysis: A promising tool for high-resolution temperature and pH reconstruction - Zifei Yang; Christopher D. Standish; Rachel M. Brown; Patrick A. Rafter; Malcolm B. Hart; Tali L. Babila; Gavin L. Foster (Chemical Geology, 2026)

An actinopterygian-dominated fish fauna from the Upper Cretaceous Williams Fork Formation, northwestern Colorado, and evidence for provinciality across Laramidia at the Campanian/Maastrichtian boundary - Joel Crothers; Jaelyn Eberle; Donald Brinkman; Alyssa Wurtz; Andrew B. Heckert; ReBecca K. Hunt-Foster; John R. Foster; Ida C. Dirkes; Renee Dunn (Cretaceous Research, 2026)

Peripheral microRNA signature in genetic frontotemporal dementia—findings from the GENFI initiative - Chiara Fenoglio; Maria Serpente; Marina Arcaro; Tiziana Carandini; Luca Sacchi; Manuela Pintus; Vittoria Borracci; Giulia Giudici; Marta Rigoni; Paola Muti; Laura Ghezzi; Arabella Bouzigues; et al. (GeroScience, 2026)
Frontotemporal dementia (FTD) is a neurodegenerative disease characterized by significant clinical and genetic heterogeneity, with approximately 40% of cases linked to hereditary genetic mutations, including MAPT , GRN , and C9ORF72 . Recently, microRNAs (miRNAs) have emerged as key regulators of cellular processes related to neurodegeneration and as potential biomarkers for FTD. However, their relevance in presymptomatic stages remains poorly understood. We conducted a miRNA expression analysis using TaqMan OpenArray® panels on blood samples collected from 171 individuals, including symptomatic mutation carriers (SMC), presymptomatic carriers (PMC), and healthy non-carriers (NC). Dysregulated miRNAs were validated and bioinformatic tools were used to identify potential associated molecular pathways. In C9ORF72 , miR-20b-5p and miR-223-5p were significantly upregulated in SMC (fold regulation over NC: 2.418 p = 0.0336 and 7.829 p < 0.0264 respectively) and PMC (5.518, p < 0.0001 and 3.941, p < 0.0001 respectively). In GRN mutation carriers, miR-28-3p was altered in both SMC and PMC (fold regulation over NC: 1.484 p < 0.050 and 3.287, p < 0.050). In MAPT mutation carriers, miR-28-5p, miR-192-3p, miR-25-3p, and miR-532-3p were altered only in SMC (fold regulation over NC: 1.496 p < 0.050, 1.911 p = 0.006, 1.468 p < 0.05, and 0.728 p < 0.05). Bioinformatic analysis revealed enrichment of pathways related to neurodegeneration and synapse impairment. These results suggest that miRNA expression levels are deregulated in mutated SMC, in C9ORF72 and GRN PMC. Notably, miR-20b-5p, miR-223-5p, and miR-28-3p were increased in preclinical stages of the disease, supporting their role as early biomarkers for C9ORF72 -FTD and GRN -FTD. Conversely, alterations in MAPT carriers appeared only in symptomatic stages, suggesting a different involvement in disease progression.

Robin Helby (1938–2024) – a giant of Australasian palynology - James B. Riding; Clinton B. Foster; Carey Hannaford; Mike Macphail; Daniel J. Mantle; Geoffrey Playford; Jill Stevens; Geoff Wood (Palynology, 2026)

Double cropping and tillage intensity in continuous wheat agroecosystems have variable impacts on soil hydrologic and physical properties - Perejitei E. Bekewe; Joseph A. Burke; Jamie L. Foster; Katie L. Lewis; Haly L. Neely; Clark B. Neely; Lauren E. Tomlin; Brandon Gerrish; Thomas W. Boutton (Soil and Tillage Research, 2026)

Development of new global lake brGDGT-temperature calibrations: advances, applications, challenges, and recommendations - Emma J. Pearson; Steve Juggins; Harry Allbrook; Louise C. Foster; Dominic A. Hodgson; B. David A. Naafs; Tony Phillips; Stephen J. Roberts (Quaternary Science Reviews, 2025)

Sintering dynamics of fine-grained rhyolitic obsidian particles from Hrafntinnuhryggur (Krafla, Iceland) with implications for silicic volcanic eruptions - Annabelle Foster; Fabian B. Wadsworth; Jérémie Vasseur; Madeleine C.S. Humphreys; Hugh Tuffen; Donald B. Dingwell; Katherine J. Dobson (Journal of Volcanology and Geothermal Research, 2025)

Assessing the role of anoxia as a potential extinction driver in the shallow marine Neotethys during the Permian-Triassic mass extinction - Anja B. Frank; Baran Karapunar; Stephen E. Grasby; Erdal Koşun; Niko Lahajnar; Mónica Alejandra Gómez Correa; Stella Z. Buchwald; Marc Metzke; William J. Foster (Chemical Geology, 2025)

A Comparison of Acute Blood Glucose Response to 2% Lactaid Milk vs. 2% Regular Milk in Non-diabetic Adults - A. Kim; B. Vanyo; L. Foster-Nicholas; L. Ji; C. Kosch (Journal of the Academy of Nutrition and Dietetics, 2025)

GDF-15 - Implications for Bladder Cancer Care and Symptom Control - B. Foster; R. Vargas; P. Srinivasan; D. Koestler; M. Bechtel; J. Holzbeierlein; M. Fisch; N. Henry; J. Unger; J. Hamilton-Reeves (Journal of the Academy of Nutrition and Dietetics, 2025)

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Purification of uranium tetrafluoride using ammonium bifluoride - Kyle R. Foster; Juliano Schorne-Pinto; Ronald E. Booth; Annabelle Husek; Mina Aziziha; Hunter B. Tisdale; Bernie W.N. Fitzpatrick; Hans-Conrad zur Loye; Markus H.A. Piro; Theodore M. Besmann (Journal of Fluorine Chemistry, 2025)

Proteomic Investigation of Neurotrophic trans-Banglene Reveals Potential Link to Iron Homeostasis - Piyumi B. Wijesiri Gunawardana; Khyati Gohil; Kyung-Mee Moon; Leonard J. Foster; Florence J. Williams (Molecular Neurobiology, 2025)

Coverage matters: identifying and mitigating sampling frame issues in recreational fishing surveys - S. M. Taylor; A. de Groote; K. Hyder; J. H. Vølstad; B. W. Hartill; J. Foster; R. Andrews; K. L. Ryan (Reviews in Fish Biology and Fisheries, 2025)
Surveys play an integral part in monitoring and maintaining sustainable recreational fisheries. For any probabilistic survey, the selection of a sampling frame (e.g., list of individuals or fishers) is an important decision because it influences the ability to provide unbiased estimates of recreational catch and effort. Undercoverage occurs when units of the target population (i.e., the population of interest) are missing from the frame population. This error can undermine the reliability of research advice generated from survey estimates. In this review, we: (i) define six sampling frame configurations that are commonly applied in probabilistic recreational fishing surveys; (ii) synthesise how coverage errors associated with each configuration have been addressed for marine recreational fisheries globally; (iii) outline approaches to identify and correct for coverage errors; and (iv) recommend how to future-proof coverage issues. In our six case studies, multiple types of undercoverage were identified and addressed to varying extents, depending on the characteristics of each fishery and type of sampling frame used. Generalised list frames (particularly phone lists) are arguably the most prone to undercoverage error. To assist in future-proofing surveys, we recommend: (1) considering coverage error during survey planning; (2) designing pilot surveys or scheduling concurrent surveys to evaluate and/or correct for potential bias; (3) recognising that coverage error often changes through time; (4) using technological or multi-frame approaches to mitigate coverage error; (5) considering model-based survey tools to correct for undercoverage; and (6) documenting the sampling frame and potential sources of coverage error in publications. These recommendations extend to inland recreational fisheries, commercial fishing surveys and fisheries-independent surveys. Graphical abstract

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

International Consortium to Classify Ageing-related Pathologies (ICCARP) senescence definitions: achieving international consensus - Emma Short; Robert T. R. Huckstepp; Kambiz Alavian; Winfried M. K. Amoaku; Thomas M. Barber; Edwin J. R. van Beek; Emyr Benbow; Sunil Bhandari; Phillip Bloom; Carlo Cota; Paul Chazot; Gary Christopher; et al. (GeroScience, 2025)

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

The viscous-brittle transition in flowing crystal-bearing volcanic dome lavas - Fabian B. Wadsworth; Jérémie Vasseur; Michael J. Heap; Jackie E. Kendrick; Claire E. Harnett; Annabelle Foster; Daniel Weller; Bettina Scheu; Anthony Lamur; Luiz Pereira; Donald B. Dingwell; Yan Lavallée (Journal of Volcanology and Geothermal Research, 2025)

Pedigree tracing to determine the origins of the modern Palomino Horse Breeders of America stock-type horse - B. Pepper; E. North; M. Foster; J. Culwell; M.C. Nicodemus; C. Cavinder; K. Harvey; T. Williams (Journal of Equine Veterinary Science, 2024)

Effects of fruit novelty on feeding preference in four globally invasive frugivorous birds - Samuel B. Case; Kapua Kawelo; Josephine Hoh; Dylan O’hearn; Jinelle H. Sperry; Jeffrey T. Foster; Donald R. Drake; Jeferson Vizentin-Bugoni; J. Patrick Kelley; Corey E. Tarwater (Biological Invasions, 2024)

The rheology of rhyolite magma from the IDDP-1 borehole and Hrafntinnuhryggur (Krafla, Iceland) with implications for geothermal drilling - Fabian B. Wadsworth; Jérémie Vasseur; Yan Lavallée; Kai-Uwe Hess; Jackie E. Kendrick; Jonathan M. Castro; Daniel Weidendorfer; Shane M. Rooyakkers; Annabelle Foster; Lucy E. Jackson; Ben M. Kennedy; Alexander R.L. Nichols; et al. (Journal of Volcanology and Geothermal Research, 2024)

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

A practical approach to meeting national obligations for sustainable trade under CITES - Tanvi Vaidyanathan; Sarah J. Foster; B. Ramkumar; Amanda C. J. Vincent (Conservation Biology, 2024)
Reconciling conservation goals with sustainable resource use requires adaptive management strategies. The Convention on International Trade in Endangered Species of Wild Fauna and Flora (CITES) regulates global trade for species listed on Appendix II, partly by requiring member countries (parties) to ensure exports do not damage wild populations (called making positive “nondetriment findings” [NDFs]). Unfortunately, when parties find NDFs difficult, they often suspend legal trade, imposing economic costs and driving trade underground. To make it easier for parties to examine the detrimental nature of exports, we devised a spatial approach and applied it to seahorses ( Hippocampus spp.) in Tamil Nadu, India, as an example. Our approach involves mapping answers to 5 key questions on species distribution (QA), pressures (QB), management measures (QC), management implementation (QD), and species’ population status (QE). We gathered data from fisher interviews and published literature. Seahorse abundance was greatest in southern Palk Bay and the northern Gulf of Mannar, primarily in seagrasses and coral reefs (QA). Fishing pressure was highest in Palk Bay, primarily from bottom trawlers and dragnetters operating in shallow seahorse habitats near the coastline (QB). Management measures including a marine protected area (MPA), bottom trawl exclusion zone, and closed season were theoretically in place (QC), but their implementation was poor (QD). Fishers reported seahorse catches in 85% of the area covered by the MPA and the exclusion zone; bottom trawlers were responsible for most violations. Seahorses were also captured in Sri Lankan waters, where bottom trawling is banned. Fisher reports indicated declining seahorse catches and reduced body sizes (QE), highlighting unsustainable exploitation. Our results highlight the need for better implementation of existing management measures before a positive NDF can be made and suggest mitigation beyond bans. Such pragmatic spatial analyses can help regulate exports at sustainable levels, supporting CITES implementation for its vast range of species.

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Defining an ageing-related pathology, disease or syndrome: International Consensus Statement - Emma Short; Ian M. Adcock; Bilal Al-Sarireh; Ann Ager; Ramzi Ajjan; Naveed Akbar; Michael A. Akeroyd; Ghada Alsaleh; Ghada Al-Sharbatee; Kambiz Alavian; Winfried Amoaku; Julie Andersen; et al. (GeroScience, 2024)
Around the world, individuals are living longer, but an increased average lifespan does not always equate to an increased health span. With advancing age, the increased prevalence of ageing-related diseases can have a significant impact on health status, functional capacity and quality of life. It is therefore vital to develop comprehensive classification and staging systems for ageing-related pathologies, diseases and syndromes. This will allow societies to better identify, quantify, understand and meet the healthcare, workforce, well-being and socioeconomic needs of ageing populations, whilst supporting the development and utilisation of interventions to prevent or to slow, halt or reverse the progression of ageing-related pathologies. The foundation for developing such classification and staging systems is to define the scope of what constitutes an ageing-related pathology, disease or syndrome. To this end, a consensus meeting was hosted by the International Consortium to Classify Ageing-Related Pathologies (ICCARP), on February 19, 2024, in Cardiff, UK, and was attended by 150 recognised experts. Discussions and voting were centred on provisional criteria that had been distributed prior to the meeting. The participants debated and voted on these. Each criterion required a consensus agreement of ≥ 70% for approval. The accepted criteria for an ageing-related pathology, disease or syndrome were (1) develops and/or progresses with increasing chronological age; (2) should be associated with, or contribute to, functional decline or an increased susceptibility to functional decline and (3) evidenced by studies in humans. Criteria for an ageing-related pathology, disease or syndrome have been agreed by an international consortium of subject experts. These criteria will now be used by the ICCARP for the classification and ultimately staging of ageing-related pathologies, diseases and syndromes.

Constitutive and numerical modelling for timber-metal connections under large deformations - L. M. Milindu B. Jayasekara; Robert M. Foster (Engineering Structures, 2024)

Deliberately introduced dung beetles in A ustralia: 12 years of occurrence and abundance records from 2001 to 2022 - Jacob D. Berson; Penelope B. Edwards; T. James Ridsdill‐Smith; Christopher K. Taylor; Daniel J. Anderson; Nigel R. Andrew; Russell A. Barrow; David A. Cousins; Robert N. Emery; Laura L. Fagan; Rhiannon M. Foster; Lucas G. Harwood; et al. (Ecology, 2024)
Since 1968, the Australian Dung Beetle Project has carried out field releases of 43 deliberately introduced dung beetle species for the biological control of livestock dung and dung‐breeding pests. Of these, 23 species are known to have become established. For most of these species, sufficient time has elapsed for population expansion to fill the extent of their potential geographic range through both natural and human‐assisted dispersal. Consequently, over the last 20 years, extensive efforts have been made to quantify the current distribution of these introduced dung beetles, as well as the seasonal and spatial variation in their activity levels. Much of these data and their associated metadata have remained unpublished, and they have not previously been synthesized into a cohesive dataset. Here, we collate and report data from the three largest dung beetle monitoring projects from 2001 to 2022. Together, these projects encompass data collected from across Australia, and include records for all 23 species of established dung beetles introduced for biocontrol purposes. In total, these data include 22,718 presence records and 213,538 absence records collected during 10,272 sampling events at 546 locations. Most presence records (97%) include abundance data. In total, 1,752,807 dung beetles were identified as part of these data. The distributional occurrence and abundance data can be used to explore questions such as factors influencing dung beetle species distributions, dung beetle biocontrol, and insect‐mediated ecosystem services. These data are provided under a CC‐BY‐NC 4.0 license and users are encouraged to cite this data paper when using the data.

Influence of habitat features on the colonisation of native and non-indigenous species - Nina Schaefer; Melanie J. Bishop; Ana B. Bugnot; Cian Foster-Thorpe; Brett Herbert; Andrew S. Hoey; Mariana Mayer-Pinto; Shinichi Nakagawa; Craig D.H. Sherman; Maria L. Vozzo; Katherine A. Dafforn (Marine Environmental Research, 2024)

Organic carbon accumulation in British saltmarshes - Craig Smeaton; Ed Garrett; Martha B. Koot; Cai J.T. Ladd; Lucy C. Miller; Lucy McMahon; Bradley Foster; Natasha L.M. Barlow; William Blake; W. Roland Gehrels; Martin W. Skov; William E.N. Austin (Science of The Total Environment, 2024)

Fine mapping of major QTL qshgd1 for spontaneous haploid genome doubling in maize (Zea mays L.) - Tyler L. Foster; Monika Kloiber-Maitz; Laurine Gilles; Ursula K. Frei; Sarah Pfeffer; Yu-Ru Chen; Somak Dutta; Arun S. Seetharam; Matthew B. Hufford; Thomas Lübberstedt (Theoretical and Applied Genetics, 2024)

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Journals must expand access to peer review data - Olivia M. Smith; Kayla L. Davis; Robin Waterman; Riley B. Pizza; Caitlin Mack; Emily E. Conway; Kara C. Dobson; Brianna Foster; Ani E. Hristova; Julie C. Jarvey; Nan Nourn; Courtney L. Davis (Trends in Ecology & Evolution, 2024)

Variable effects of substrate colour and microtexture on sessile marine taxa in Australian estuaries - Nina Schaefer; Melanie J. Bishop; Ana B. Bugnot; Brett Herbert; Andrew S. Hoey; Mariana Mayer-Pinto; Craig D. H. Sherman; Cian Foster-Thorpe; Maria L. Vozzo; Katherine A. Dafforn (Biofouling, 2024)

A multi-region study of carbonate clumped isotope data from terrestrial snails - H.L. Bricker; J.B. Bateman; B. Elliott; B.A. Mitsunaga; J. Mering; I.S. Foster; Y. Yanes; E.A. Oches; R.A. Eagle; A. Tripati (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

P25-14: Hepatic safety assessment of covalent inhibitor drug candidates - S. Amberntsson; B. Chouhan; A. Foster; G. Smith; S. Wilkinson; S. Harlfinger; S. Kavanagh; D. Williams (Toxicology Letters, 2023)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Correction: Impact of nitrogen (N) and phosphorus (P) enrichment and skewed N:P stoichiometry on the skeletal formation and microstructure of symbiotic reef corals - M. C. Buckingham; C. D’Angelo; T. B. Chalk; G. L. Foster; K. G. Johnson; Z. Connelly; C. Olla; M. Saeed; J. Wiedenmann (Coral Reefs, 2023)

Temporal dynamics of soil fungi in a pyrodiverse dry‐sclerophyll forest - Elle J. Bowd; Eleonora Egidi; David B. Lindenmayer; David A. Wardle; Paul Kardol; Claire Foster (Molecular Ecology, 2023)
Fire is a major evolutionary and ecological driver that shapes biodiversity in forests. While above‐ground community responses to fire have been well‐documented, those below‐ground are much less understood. However, below‐ground communities, including fungi, play key roles in forests and facilitate the recovery of other organisms after fire. Here, we used internal transcribed spacer (ITS) meta‐barcoding data from forests with three different times since fire [short (3 years), medium (13–19 years) and long (>26 years)] to characterize the temporal responses of soil fungal communities across functional groups, ectomycorrhizal exploration strategies and inter‐guild associations. Our findings indicate that fire effects on fungal communities are strongest in the short to medium term, with clear distinctions between communities in forests with a short time (3 years) since fire, a medium time (13–19 years) and a long time (>26 years) since fire. Ectomycorrhizal fungi were disproportionately impacted by fire relative to saprotrophs, but the direction of the response varied depending on morphological structures and exploration strategies. For instance, short‐distance ectomycorrhizal fungi increased with recent fire, while medium‐distance (fringe) ectomycorrhizal fungi decreased. Further, we detected strong, negative inter‐guild associations between ectomycorrhizal and saprotrophic fungi but only at medium and long times since fire. Given the functional significance of fungi, the temporal changes in fungal composition, inter‐guild associations and functional groups after fire demonstrated in our study may have functional implications that require adaptive management to curtail.

Phylogenetic characterization of Orthobunyaviruses isolated from Trinidad shows evidence of natural reassortment - Jerome E. Foster; Krisangel López; Gillian Eastwood; Hilda Guzman; Christine V. F. Carrington; Robert B. Tesh; Albert J. Auguste (Virus Genes, 2023)
The genus Orthobunyavirus is a diverse group of viruses in the family Peribunyaviridae , recently classified into 20 serogroups, and 103 virus species. Although most viruses within these serogroups are phylogenetically distinct, the absence of complete genome sequences has left several viruses incompletely characterized. Here we report the complete genome sequences for 11 orthobunyaviruses isolated from Trinidad, French Guiana, Guatemala, and Panama that were serologically classified into six serogroups and 10 species. Phylogenetic analyses of these 11 newly derived sequences indicate that viruses belonging to the Patois, Capim, Guama, and Group C serocomplexes all have a close genetic origin. We show that three of the 11 orthobunyaviruses characterized (belonging to the Group C and Bunyamwera serogroups) have evidence of histories of natural reassortment through the M genome segment. Our data also suggests that two distinct lineages of Group C viruses concurrently circulate in Trinidad and are transmitted by the same mosquito vectors. This study also highlights the importance of complementing serological identification with nucleotide sequencing when characterizing orthobunyaviruses.

The exposed Mule Creek vent deposits record the structure of a volcanic conduit during a hybrid explosive–effusive eruption - Holly E. Unwin; Hugh Tuffen; Fabian B. Wadsworth; Emrys R. Phillips; Mike R. James; Annabelle Foster; Stephan Kolzenburg; Jonathan M. Castro; Lucy A. Porritt (Bulletin of Volcanology, 2023)
Silicic volcanic eruptions commonly begin with the explosive ejection of pyroclastic material, before transitioning to gentler effusion-dominated activity. Well-exposed dissected silicic systems are scarce and poorly studied, hindering the advances in our understanding of the explosive–effusive transition needed to improve interpretations of volcanic unrest and hazard forecasting. The Mule Creek vent (New Mexico, USA) is a dissected silicic conduit that records the processes controlling conduit formation and evolution, and the role tuffisites (fractures filled with variably welded pyroclasts) play in conduit dynamics. Here, we use decimeter-scale photo-mapping of lithostratigraphic units and thin section analysis to differentiate and interpret three dominant emplacement styles during vent evolution. First, there was repeated deposition and erosion of pyroclastic material at the conduit walls, recorded by erosive surfaces in pyroclastic breccia and agglomerates at the conduit margins. Second, sub-vertical domains of dense melt-dominated magma were emplaced and preserved as glass-dominated vitrophyre and brecciated vitrophyre, with the textural hallmarks of assembly from welding of pyroclasts. Finally, the sub-horizontal fracturing of previously deposited lithologies produced laterally cross-cutting tuffisites. The vent deposits track the widening and then narrowing of the conduit through time and reflect progressive insulation and generally higher temperatures towards the conduit center as pyroclasts accumulate. Welding of pyroclastic fill and the formation of dense vitrophyres towards the conduit center lowers deposit porosity and effective wall permeability. This drives localized gas pressure increases and results in gas-driven fracturing, generating tuffisites, which act as transient outgassing pathways. The structure of the Mule Creek vent records an explosive–effusive transition, constraining the processes controlling conduit evolution and aiding our interpretation of volcanic unrest.

Boron isotopes in blue diamond record seawater-derived fluids in the lower mantle - Margo E. Regier; Karen V. Smit; Thomas B. Chalk; Thomas Stachel; Richard A. Stern; Evan M. Smith; Gavin L. Foster; Yannick Bussweiler; Chris DeBuhr; Antony D. Burnham; Jeff W. Harris; D. Graham Pearson (Earth and Planetary Science Letters, 2023)

Vector species, pasture legume host range, and impact on grain legumes of an Australian soybean dwarf virus isolate - B. S. Congdon; J. R. Baulch; K. J. Foster (Archives of Virology, 2023)

Introduced galliforms as seed predators and dispersers in Hawaiian forests - Samuel B. Case; Katherine Postelli; Donald R. Drake; Jeferson Vizentin-Bugoni; Jeffrey T. Foster; Jinelle H. Sperry; J. Patrick Kelley; Corey E. Tarwater (Biological Invasions, 2022)

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Impact of nitrogen (N) and phosphorus (P) enrichment and skewed N:P stoichiometry on the skeletal formation and microstructure of symbiotic reef corals - M. C. Buckingham; C. D’Angelo; T. B. Chalk; G. L. Foster; K. G. Johnson; Z. Connelly; C. Olla; M. Saeed; J. Wiedenmann (Coral Reefs, 2022)
Reported divergent responses of coral growth and skeletal microstructure to the nutrient environment complicate knowledge-based management of water quality in coral reefs. By re-evaluating published results considering the taxonomy of the studied corals and the N:P stoichiometry of their nutrient environment, we could resolve some of the major apparent contradictions. Our analysis suggests that Acroporids behave differently to several other common genera and show distinct responses to specific nutrient treatments. We hypothesised that both the concentrations of dissolved inorganic N and P in the water and their stoichiometry shape skeletal growth and microstructure. We tested this hypothesis by exposing Acropora polystoma fragments to four nutrient treatments for > 10 weeks: high nitrate/high phosphate (HNHP), high nitrate/low phosphate (HNLP), low nitrate/high phosphate (LNHP) and low nitrate/low phosphate (LNLP). HNHP corals retained high zooxanthellae densities and their linear extension and calcification rates were up to ten times higher than in the other treatments. HNLP and LNLP corals bleached through loss of symbionts. The photochemical efficiency (Fv/Fm) of residual symbionts in HNLP corals was significantly reduced, indicating P-starvation. Micro-computed tomography (µCT) of the skeletal microstructure revealed that reduced linear extension in nutrient limited or nutrient starved conditions (HNLP, LNHP, LNLP) was associated with significant thickening of skeletal elements and reduced porosity. These changes can be explained by the strongly reduced linear extension rate in combination with a smaller reduction in the calcification rate. Studies using increased skeletal density as a proxy for past thermal bleaching events should consider that such an increase in density may also be associated with temperature-independent response to the nutrient environment. Furthermore, the taxonomy of corals and seawater N:P stoichiometry should be considered when analysing and managing the impacts of nutrient pollution.

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Plant performance responds to intraspecific variation in soil inocula from individual Solidago clones - Bryan S. Foster; Brendan B. Haile; Justin T. Campnell; Thomas Canam; Marci J. Gallagher; Scott J. Meiners (Plant Ecology, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Determinants of community compositional change are equally affected by global change - Meghan L. Avolio; Kimberly J. Komatsu; Scott L. Collins; Emily Grman; Sally E. Koerner; Andrew T. Tredennick; Kevin R. Wilcox; Sara Baer; Elizabeth H. Boughton; Andrea J. Britton; Bryan Foster; Laura Gough; et al. (Ecology Letters, 2021)
Global change is impacting plant community composition, but the mechanisms underlying these changes are unclear. Using a dataset of 58 global change experiments, we tested the five fundamental mechanisms of community change: changes in evenness and richness, reordering, species gains and losses. We found 71% of communities were impacted by global change treatments, and 88% of communities that were exposed to two or more global change drivers were impacted. Further, all mechanisms of change were equally likely to be affected by global change treatments—species losses and changes in richness were just as common as species gains and reordering. We also found no evidence of a progression of community changes, for example, reordering and changes in evenness did not precede species gains and losses. We demonstrate that all processes underlying plant community composition changes are equally affected by treatments and often occur simultaneously, necessitating a wholistic approach to quantifying community changes.

A review of a decade of lessons from one of the world’s largest MPAs: conservation gains and key challenges - Graeme C. Hays; Heather J. Koldewey; Samantha Andrzejaczek; Martin J. Attrill; Shanta Barley; Daniel T. I. Bayley; Cassandra E. Benkwitt; Barbara Block; Robert J. Schallert; Aaron B. Carlisle; Pete Carr; Taylor K. Chapple; et al. (Marine Biology, 2020)

Emergence of an evolutionary innovation: Gene expression differences associated with the transition between oviparity and viviparity - Charles S. P. Foster; Michael B. Thompson; James U. Van Dyke; Matthew C. Brandley; Camilla M. Whittington (Molecular Ecology, 2020)
Our understanding of the evolution of complex biological traits is greatly advanced by examining taxa with intermediate phenotypes. The transition from oviparity (egg‐laying) to viviparity (live‐bearing) has occurred independently in many animal lineages, but there are few phenotypic intermediates. The lizard Saiphos equalis exhibits bimodal reproduction, with some viviparous populations, and other oviparous populations with long egg‐retention, a rare trait where most of embryonic development occurs inside the mother prior to late ovipositioning. We posit that oviparous S. equalis represent an intermediate form between “true” oviparity and viviparity. We used transcriptomics to compare uterine gene expression in these two phenotypes, and provide a molecular model for the genetic control and evolution of reproductive mode. Many genes are differentially expressed throughout the reproductive cycle of both phenotypes, which have clearly different gene expression profiles overall. The differentially expressed genes within oviparous and viviparous individuals have broadly similar biological functions putatively important for sustaining embryos, including uterine remodelling, respiratory gas and water exchange, and immune regulation. These functional similarities indicate either that long egg‐retention is an exaptation for viviparity, or might reflect parallel evolution of similar gravidity‐related changes in gene expression in long egg‐retention oviparity. In contrast, gene expression changes across the reproductive cycle of long egg‐retaining oviparous S. equalis are dramatically different from those of “true” oviparous skinks (such as Lampropholis guichenoti ), supporting our assertion that oviparous S. equalis exhibit an intermediate phenotype between “true” oviparity and viviparity.

The descending motor tracts are different in dancers and musicians - Chiara Giacosa; Falisha J. Karpati; Nicholas E. V. Foster; Krista L. Hyde; Virginia B. Penhune (Brain Structure and Function, 2019)

The state of Western Australia’s coral reefs - James P. Gilmour; Kylie L. Cook; Nicole M. Ryan; Marjetta L. Puotinen; Rebecca H. Green; George Shedrawi; Jean-Paul A. Hobbs; Damian P. Thomson; Russell C. Babcock; Joanna Buckee; Taryn Foster; Zoe T. Richards; et al. (Coral Reefs, 2019)

Trends and indicators for quantifying moth abundance and occupancy in Scotland - E. B. Dennis; T. M. Brereton; B. J. T. Morgan; R. Fox; C. R. Shortall; T. Prescott; S. Foster (Journal of Insect Conservation, 2019)

Integrated in vitro models for hepatic safety and metabolism: evaluation of a human Liver-Chip and liver spheroid - Alison J. Foster; Bhavik Chouhan; Sophie L. Regan; Helen Rollison; Sara Amberntsson; Linda C. Andersson; Abhishek Srivastava; Malin Darnell; Jonathan Cairns; Stanley E. Lazic; Kyung-Jin Jang; Debora B. Petropolis; et al. (Archives of Toxicology, 2019)

Sedimentary profiles of pollution marker chemicals along a large tributary of Chesapeake Bay (mid-Atlantic USA) - Gregory D. Foster; Cassi Walls; Phillip R. McEachern; Thomas B. Huff; Randolph McBride (Journal of Soils and Sediments, 2019)

Weather effects on birds of different size are mediated by long‐term climate and vegetation type in endangered temperate woodlands - David B. Lindenmayer; Peter Lane; Mason Crane; Daniel Florance; Claire N. Foster; Karen Ikin; Damian Michael; Chloe F. Sato; Ben C. Scheele; Martin J. Westgate (Global Change Biology, 2019)
Species occurrence is influenced by a range of factors including habitat attributes, climate, weather, and human landscape modification. These drivers are likely to interact, but their effects are frequently quantified independently. Here, we report the results of a 13‐year study of temperate woodland birds in south‐eastern Australia to quantify how different‐sized birds respond to the interacting effects of: (a) short‐term weather (rainfall and temperature in the 12 months preceding our surveys), (b) long‐term climate (average rainfall and maximum and minimum temperatures over the period 1970–2014), and (c) broad structural forms of vegetation (old‐growth woodland, regrowth woodland, and restoration plantings). We uncovered significant interactions between bird body size, vegetation type, climate, and weather. High short‐term rainfall was associated with decreased occurrence of large birds in old‐growth and regrowth woodland, but not in restoration plantings. Conversely, small bird occurrence peaked in wet years, but this effect was most pronounced in locations with a history of high rainfall, and was actually reversed (peak occurrence in dry years) in restoration plantings in dry climates. The occurrence of small birds was depressed—and large birds elevated—in hot years, except in restoration plantings which supported few large birds under these circumstances. Our investigation suggests that different mechanisms may underpin contrasting responses of small and large birds to the interacting effects of climate, weather, and vegetation type. A diversity of vegetation cover is needed across a landscape to promote the occurrence of different‐sized bird species in agriculture‐dominated landscapes, particularly under variable weather conditions. Climate change is predicted to lead to widespread drying of our study region, and restoration plantings—especially currently climatically wet areas—may become critically important for conserving bird species, particularly small‐bodied taxa.

Analysis of novel domain-specific mutations in the zebrafish ndr2/cyclops gene generated using CRISPR-Cas9 RNPs - Ashley N. Turner; Reagan S. Andersen; Ivy E. Bookout; Lauren N. Brashear; James C. Davis; David M. Gahan; John P. Gotham; Baraa A. Hijaz; Ashish S. Kaushik; Jordan B. Mcgill; Victoria L. Miller; Zachariah P. Moseley; et al. (Journal of Genetics, 2018)

Ambient changes exceed treatment effects on plant species abundance in global change experiments - J. Adam Langley; Samantha K. Chapman; Kimberly J. La Pierre; Meghan Avolio; William D. Bowman; David S. Johnson; Forest Isbell; Kevin R. Wilcox; Bryan L. Foster; Mark J. Hovenden; Alan K. Knapp; Sally E. Koerner; et al. (Global Change Biology, 2018)
The responses of species to environmental changes will determine future community composition and ecosystem function. Many syntheses of global change experiments examine the magnitude of treatment effect sizes, but we lack an understanding of how plant responses to treatments compare to ongoing changes in the unmanipulated (ambient or background) system. We used a database of long‐term global change studies manipulating CO 2 , nutrients, water, and temperature to answer three questions: (a) How do changes in plant species abundance in ambient plots relate to those in treated plots? (b) How does the magnitude of ambient change in species‐level abundance over time relate to responsiveness to global change treatments? (c) Does the direction of species‐level responses to global change treatments differ from the direction of ambient change? We estimated temporal trends in plant abundance for 791 plant species in ambient and treated plots across 16 long‐term global change experiments yielding 2,116 experiment–species–treatment combinations. Surprisingly, for most species (57%) the magnitude of ambient change was greater than the magnitude of treatment effects. However, the direction of ambient change, whether a species was increasing or decreasing in abundance under ambient conditions, had no bearing on the direction of treatment effects. Although ambient communities are inherently dynamic, there is now widespread evidence that anthropogenic drivers are directionally altering plant communities in many ecosystems. Thus, global change treatment effects must be interpreted in the context of plant species trajectories that are likely driven by ongoing environmental changes.

Reproducible multi-parameter acoustic detection of seasonal drift macroalgae in the Indian River Lagoon, Florida - G. Foster; B. M. Riegl; L. J. Morris; K. A. Foster (Journal of Coastal Conservation, 2018)

The duality of ocean acidification as a resource and a stressor - Sean D. Connell; Zoë A. Doubleday; Nicole R. Foster; Sarah B. Hamlyn; Christopher D. G. Harley; Brian Helmuth; Brendan P. Kelaher; Ivan Nagelkerken; Kirsten L. Rodgers; Gianluca Sarà; Bayden D. Russell (Ecology, 2018)
Ecologically dominant species often define ecosystem states, but as human disturbances intensify, their subordinate counterparts increasingly displace them. We consider the duality of disturbance by examining how environmental drivers can simultaneously act as a stressor to dominant species and as a resource to subordinates. Using a model ecosystem, we demonstrate that CO 2 ‐driven interactions between species can account for such reversals in dominance; i.e., the displacement of dominants (kelp forests) by subordinates (turf algae). We established that CO 2 enrichment had a direct positive effect on productivity of turfs, but a negligible effect on kelp. CO 2 enrichment further suppressed the abundance and feeding rate of the primary grazer of turfs (sea urchins), but had an opposite effect on the minor grazer (gastropods). Thus, boosted production of subordinate producers, exacerbated by a net reduction in its consumption by primary grazers, accounts for community change (i.e., turf displacing kelp). Ecosystem collapse, therefore, is more likely when resource enrichment alters competitive dominance of producers, and consumers fail to compensate. By recognizing such duality in the responses of interacting species to disturbance, which may stabilize or exacerbate change, we can begin to understand how intensifying human disturbances determine whether or not ecosystems undergo phase shifts.

Investigating the Complex Association Between Viral Ecology, Environment, and Northeast Pacific Sea Star Wasting - Ian Hewson; Kalia S. I. Bistolas; Eva M. Quijano Cardé; Jason B. Button; Parker J. Foster; Jacob M. Flanzenbaum; Jan Kocian; Chaunte K. Lewis (Frontiers in Marine Science, 2018)

Loss of the nutrient sensor TAS1R3 leads to reduced bone resorption - Michael S. Eaton; Nicholas Weinstein; Jordan B. Newby; Maggie M. Plattes; Hanna E. Foster; Jon W. Arthur; Taylor D. Ward; Stephen R. Shively; Ryann Shor; Justin Nathan; Hannah M. Davis; Lilian I. Plotkin; et al. (Journal of Physiology and Biochemistry, 2018)

Energy conserving thermoregulatory patterns and lower disease severity in a bat resistant to the impacts of white-nose syndrome - Marianne S. Moore; Kenneth A. Field; Melissa J. Behr; Gregory G. Turner; Morgan E. Furze; Daniel W. F. Stern; Paul R. Allegra; Sarah A. Bouboulis; Chelsey D. Musante; Megan E. Vodzak; Matthew E. Biron; Melissa B. Meierhofer; et al. (Journal of Comparative Physiology B, 2018)

Simultaneous vegetation classification and mapping at large spatial scales - Mitchell B. Lyons; Scott D. Foster; David A. Keith (Journal of Biogeography, 2017)
Aim Multivariate mixture models offer the ability to streamline the typically multi‐stage process of vegetation classification and mapping into a single, simultaneous analytical step. Our aim is to demonstrate the model's utility over large and diverse areas, with comparison to existing classification and mapping conventions. Location New South Wales, Australia. Methods We demonstrate a statistical model that uses both multivariate species data and environmental covariate data to simultaneously classify observations into groups and predict those groups out into environmental and geographical space. We used two large data sets to demonstrate the method: an ~810,000 km 2 area with 4,715 sites and 488 species and a ~220,000 km 2 area with 5,183 sites and 446 species. A range of topographic, terrain, climate and soil predictors were used as environmental variables, including future projected climate variables. Models can be fit with the R package “ RCP mod.” Results The method results in probabilistic memberships to vegetation assemblages, for both the classification and map. There was general agreement between our approach and existing vegetation classification conventions, but we explore some notable differences. We were able to examine the environmental gradients that define the predicted vegetation distributions, as well as make predictions about how the distribution of species assemblages might shift as a result of climate change. Main conclusions Our approach tightens the link between description of biodiversity patterns and their depiction in space, by considering both biotic and spatially explicit abiotic information simultaneously. The method allows uncertainty to be quantified objectively across a consistent set of groups for both vegetation classification and mapping, which is rarely the case in traditional multi‐stage approaches. A simultaneous modelling approach increases capacity to make predictions into varying spatial, temporal and environmental dimensions, providing new ecological insights and increasing capacity for evidence‐based decision making.

Lessons on Climate Sensitivity From Past Climate Changes - Anna S. von der Heydt; Henk A. Dijkstra; Roderik S. W. van de Wal; Rodrigo Caballero; Michel Crucifix; Gavin L. Foster; Matthew Huber; Peter Köhler; Eelco Rohling; Paul J. Valdes; Peter Ashwin; Sebastian Bathiany; et al. (Current Climate Change Reports, 2016)

Functional analysis of Agaricus bisporus serine proteinase 1 reveals roles in utilization of humic rich substrates and adaptation to the leaf‐litter ecological niche - Mary N. Heneghan; Claire Burns; Ana M. S. B. Costa; Kerry S. Burton; Michael P. Challen; Andy M. Bailey; Gary D. Foster (Environmental Microbiology, 2016)
Summary Agaricus bisporus is a secondary decomposer fungus and an excellent model for the adaptation, persistence and growth of fungi in humic‐rich environments such as soils of temperate woodland and pastures. The A. bisporus serine proteinase SPR1 is induced by humic acids and is highly expressed during growth on compost. Three Spr1 gene silencing cassettes were constructed around sense, antisense and non‐translatable‐stop strategies (pGRsensehph, pGRantihph and pGRstophph). Transformation of A. bisporus with these cassettes generated cultures showing a reduction in extracellular proteinase activity as demonstrated by the reduction, or abolition, of a clearing zone on plate‐based bioassays. These lines were then assessed by detailed enzyme assay, RT‐qPCR and fruiting. Serine proteinase activity in liquid cultures was reduced in 83% of transformants. RT‐qPCR showed reduced Spr1 mRNA levels in all transformants analysed, and these correlated with reduced enzyme activity. When fruiting was induced, highly‐silenced transformant AS5 failed to colonize the compost, whilst for those that did colonize the compost, 60% gave a reduction in mushroom yield. Transcriptional, biochemical and developmental observations, demonstrate that SPR1 has an important role in nutrient acquisition in compost and that SPR1 is a key enzyme in the adaptation of Agaricus to the humic‐rich ecological niche formed during biomass degradation.

The effect of high dose oral manganese exposure on copper, iron and zinc levels in rats - Courtney J. Mercadante; Carolina Herrera; Michael A. Pettiglio; Melanie L. Foster; Laura C. Johnson; David C. Dorman; Thomas B. Bartnikas (BioMetals, 2016)

Predicting tree biomass growth in the temperate–boreal ecotone: Is tree size, age, competition, or climate response most important? - Jane R. Foster; Andrew O. Finley; Anthony W. D'Amato; John B. Bradford; Sudipto Banerjee (Global Change Biology, 2016)
As global temperatures rise, variation in annual climate is also changing, with unknown consequences for forest biomes. Growing forests have the ability to capture atmospheric CO 2 and thereby slow rising CO 2 concentrations. Forests’ ongoing ability to sequester C depends on how tree communities respond to changes in climate variation. Much of what we know about tree and forest response to climate variation comes from tree‐ring records. Yet typical tree‐ring datasets and models do not capture the diversity of climate responses that exist within and among trees and species. We address this issue using a model that estimates individual tree response to climate variables while accounting for variation in individuals’ size, age, competitive status, and spatially structured latent covariates. Our model allows for inference about variance within and among species. We quantify how variables influence aboveground biomass growth of individual trees from a representative sample of 15 northern or southern tree species growing in a transition zone between boreal and temperate biomes. Individual trees varied in their growth response to fluctuating mean annual temperature and summer moisture stress. The variation among individuals within a species was wider than mean differences among species. The effects of mean temperature and summer moisture stress interacted, such that warm years produced positive responses to summer moisture availability and cool years produced negative responses. As climate models project significant increases in annual temperatures, growth of species like Acer saccharum , Quercus rubra , and Picea glauca will vary more in response to summer moisture stress than in the past. The magnitude of biomass growth variation in response to annual climate was 92–95% smaller than responses to tree size and age. This means that measuring or predicting the physical structure of current and future forests could tell us more about future C dynamics than growth responses related to climate change alone.

Hepatic effects of repeated oral administration of diclofenac to hepatic cytochrome P450 reductase null (HRN™) and wild-type mice - James A. Akingbasote; Alison J. Foster; Ian Wilson; Sunil Sarda; Huw B. Jones; J. Gerry Kenna (Archives of Toxicology, 2016)

Integrating theory into disturbance interaction experiments to better inform ecosystem management - Claire N. Foster; Chloe F. Sato; David B. Lindenmayer; Philip S. Barton (Global Change Biology, 2016)
Managing multiple, interacting disturbances is a key challenge to biodiversity conservation, and one that will only increase as global change drivers continue to alter disturbance regimes. Theoretical studies have highlighted the importance of a mechanistic understanding of stressor interactions for improving the prediction and management of interactive effects. However, many conservation studies are not designed or interpreted in the context of theory and instead focus on case‐specific management questions. This is a problem as it means that few studies test the relationships highlighted in theoretical models as being important for ecological management. We explore the extent of this problem among studies of interacting disturbances by reviewing recent experimental studies of the interaction between fire and grazing in terrestrial ecosystems. Interactions between fire and grazing can occur via a number of pathways; one disturbance can modify the other's likelihood, intensity or spatial distribution, or one disturbance can alter the other's impacts on individual organisms. The strength of such interactions will vary depending on disturbance attributes (e.g. size or intensity), and this variation is likely to be nonlinear. We show that few experiments testing fire–grazing interactions are able to identify the mechanistic pathway driving an observed interaction, and most are unable to detect nonlinear effects. We demonstrate how these limitations compromise the ability of experimental studies to effectively inform ecological management. We propose a series of adjustments to the design of disturbance interaction experiments that would enable tests of key theoretical pathways and provide the deeper ecological understanding necessary for effective management. Such considerations are relevant to studies of a broad range of ecological interactions and are critical to informing the management of disturbance regimes in the context of accelerating global change.

Sensorimotor integration is enhanced in dancers and musicians - Falisha J. Karpati; Chiara Giacosa; Nicholas E. V. Foster; Virginia B. Penhune; Krista L. Hyde (Experimental Brain Research, 2016)

Global impacts of the 1980s regime shift - Philip C. Reid; Renata E. Hari; Grégory Beaugrand; David M. Livingstone; Christoph Marty; Dietmar Straile; Jonathan Barichivich; Eric Goberville; Rita Adrian; Yasuyuki Aono; Ross Brown; James Foster; et al. (Global Change Biology, 2016)
Despite evidence from a number of Earth systems that abrupt temporal changes known as regime shifts are important, their nature, scale and mechanisms remain poorly documented and understood. Applying principal component analysis, change‐point analysis and a sequential t ‐test analysis of regime shifts to 72 time series, we confirm that the 1980s regime shift represented a major change in the Earth's biophysical systems from the upper atmosphere to the depths of the ocean and from the Arctic to the Antarctic, and occurred at slightly different times around the world. Using historical climate model simulations from the Coupled Model Intercomparison Project Phase 5 ( CMIP 5) and statistical modelling of historical temperatures, we then demonstrate that this event was triggered by rapid global warming from anthropogenic plus natural forcing, the latter associated with the recovery from the El Chichón volcanic eruption. The shift in temperature that occurred at this time is hypothesized as the main forcing for a cascade of abrupt environmental changes. Within the context of the last century or more, the 1980s event was unique in terms of its global scope and scale; our observed consequences imply that if unavoidable natural events such as major volcanic eruptions interact with anthropogenic warming unforeseen multiplier effects may occur.

Interactive effects of fire and large herbivores on web-building spiders - C. N. Foster; P. S. Barton; J. T. Wood; D. B. Lindenmayer (Oecologia, 2015)

Ploidy Level Affects Important Biomass Traits of Novel Shrub Willow (Salix) Hybrids - Michelle J. Serapiglia; Fred E. Gouker; J. Foster Hart; Faride Unda; Shawn D. Mansfield; Arthur J. Stipanovic; Lawrence B. Smart (BioEnergy Research, 2015)

CTFS ‐Forest GEO : a worldwide network monitoring forests in an era of global change - Kristina J. Anderson‐Teixeira; Stuart J. Davies; Amy C. Bennett; Erika B. Gonzalez‐Akre; Helene C. Muller‐Landau; S. Joseph Wright; Kamariah Abu Salim; Angélica M. Almeyda Zambrano; Alfonso Alonso; Jennifer L. Baltzer; Yves Basset; Norman A. Bourg; et al. (Global Change Biology, 2015)
Global change is impacting forests worldwide, threatening biodiversity and ecosystem services including climate regulation. Understanding how forests respond is critical to forest conservation and climate protection. This review describes an international network of 59 long‐term forest dynamics research sites ( CTFS ‐Forest GEO ) useful for characterizing forest responses to global change. Within very large plots (median size 25 ha), all stems ≥1 cm diameter are identified to species, mapped, and regularly recensused according to standardized protocols. CTFS ‐Forest GEO spans 25°S–61°N latitude, is generally representative of the range of bioclimatic, edaphic, and topographic conditions experienced by forests worldwide, and is the only forest monitoring network that applies a standardized protocol to each of the world's major forest biomes. Supplementary standardized measurements at subsets of the sites provide additional information on plants, animals, and ecosystem and environmental variables. CTFS ‐Forest GEO sites are experiencing multifaceted anthropogenic global change pressures including warming (average 0.61 °C), changes in precipitation (up to ±30% change), atmospheric deposition of nitrogen and sulfur compounds (up to 3.8 g N m −2 yr −1 and 3.1 g S m −2 yr −1 ), and forest fragmentation in the surrounding landscape (up to 88% reduced tree cover within 5 km). The broad suite of measurements made at CTFS ‐Forest GEO sites makes it possible to investigate the complex ways in which global change is impacting forest dynamics. Ongoing research across the CTFS ‐Forest GEO network is yielding insights into how and why the forests are changing, and continued monitoring will provide vital contributions to understanding worldwide forest diversity and dynamics in an era of global change.

mGluR5 positive allosteric modulation and its effects on MK-801 induced set-shifting impairments in a rat operant delayed matching/non-matching-to-sample task - Amber L. LaCrosse; Brian T. Burrows; Rachel M. Angulo; Phoebe R. Conrad; Sarah M. Himes; Nordia Mathews; Scott A. Wegner; Sara B. Taylor; M. Foster Olive (Psychopharmacology, 2015)

Contrast-enhanced molecular ultrasound differentiates endoglin genotypes in mouse embryos - J. M. Denbeigh; B. A. Nixon; J. J. Y. Lee; M. Jerkic; P. A. Marsden; M. Letarte; M. C. Puri; F. S. Foster (Angiogenesis, 2015)

Reducing the volume of sprint interval training does not diminish maximal and submaximal performance gains in healthy men - Jason G. E. Zelt; Paul B. Hankinson; William S. Foster; Cameron B. Williams; Julia Reynolds; Ellen Garneys; Michael E. Tschakovsky; Brendon J. Gurd (European Journal of Applied Physiology, 2014)

Changing climate and the altitudinal range of avian malaria in the Hawaiian Islands – an ongoing conservation crisis on the island of Kaua'i - Carter T. Atkinson; Ruth B. Utzurrum; Dennis A. Lapointe; Richard J. Camp; Lisa H. Crampton; Jeffrey T. Foster; Thomas W. Giambelluca (Global Change Biology, 2014)
Transmission of avian malaria in the Hawaiian Islands varies across altitudinal gradients and is greatest at elevations below 1500 m where both temperature and moisture are favorable for the sole mosquito vector, Culex quinquefasciatus , and extrinsic sporogonic development of the parasite, Plasmodium relictum . Potential consequences of global warming on this system have been recognized for over a decade with concerns that increases in mean temperatures could lead to expansion of malaria into habitats where cool temperatures currently limit transmission to highly susceptible endemic forest birds. Recent declines in two endangered species on the island of Kaua'i, the ‘Akikiki ( Oreomystis bairdi ) and ‘Akeke'e ( Loxops caeruleirostris ), and retreat of more common native honeycreepers to the last remaining high elevation habitat on the Alaka'i Plateau suggest that predicted changes in disease transmission may be occurring. We compared prevalence of malarial infections in forest birds that were sampled at three locations on the Plateau during 1994–1997 and again during 2007–2013, and also evaluated changes in the occurrence of mosquito larvae in available aquatic habitats during the same time periods. Prevalence of infection increased significantly at the lower (1100 m, 10.3% to 28.2%), middle (1250 m, 8.4% to 12.2%), and upper ends of the Plateau (1350 m, 2.0% to 19.3%). A concurrent increase in detections of Culex larvae in aquatic habitats associated with stream margins indicates that populations of the vector are also increasing. These increases are at least in part due to local transmission because overall prevalence in Kaua'i ‘Elepaio ( Chasiempis sclateri ), a sedentary native species, has increased from 17.2% to 27.0%. Increasing mean air temperatures, declining precipitation, and changes in streamflow that have taken place over the past 20 years are creating environmental conditions throughout major portions of the Alaka'i Plateau that support increased transmission of avian malaria.

Looking for age-related growth decline in natural forests: unexpected biomass patterns from tree rings and simulated mortality - Jane R. Foster; Anthony W. D’Amato; John B. Bradford (Oecologia, 2014)

Exercise-induced myofibrillar disruption with sarcolemmal integrity prior to simulated diving has no effect on vascular bubble formation in rats - Arve Jørgensen; Philip P. Foster; Ingrid Eftedal; Ulrik Wisløff; Gøran Paulsen; Marianne B. Havnes; Alf O. Brubakk (European Journal of Applied Physiology, 2013)

Viral infection of Phaeocystis globosa impedes release of chitinous star‐like structures: quantification using single cell approaches - A. R. Sheik; C. P. D. Brussaard; G. Lavik; R. A. Foster; N. Musat; B. Adam; M. M. M. Kuypers (Environmental Microbiology, 2013)
Summary Phaeocystis globosa is an ecologically important bloom‐forming phytoplankton, which sequesters substantial amounts of inorganic carbon and can form carbon‐enriched chitinous star‐like structures. Viruses infecting P. globosa (PgVs) play a significant regulatory role in population dynamics of the host species. However, the extent to which viruses alter host physiology and its carbon assimilation on single cell level is still largely unknown. This study demonstrates for the first time the impact of viral infection on carbon assimilation and cell morphology of individual axenic P. globosa cells using two single cell techniques: high resolution nanometre‐scale Secondary‐Ion Mass Spectrometry (nanoSIMS) approach and atomic force microscopy (AFM). Up until viral lysis (19 h post infection), the bulk carbon assimilation by infected P. globosa cultures was identical to the assimilation by the non‐infected cultures (33 µmol C l −1 ). However, single cell analysis showed that viral infection of P. globosa impedes the release of star‐like structures. Non‐infected cells transfer up to 44.5 µmol C l −1 (36%) of cellular biomass in the form of star‐like structures, suggesting a vital role in the survival of P. globosa cells. We hypothesize that impediment of star‐like structures in infected P. globosa cells may inactivate viral infectivity by forming flocculants after cell lysis. Moreover, we show that substantial amounts of newly produced viruses (∼ 68%) were attached to P. globosa cells prior to cell lysis. Further, we speculate that infected cells become more susceptible for grazing which provides potential reasons for the sudden disappearance of PgVs in the environment. The scenarios of enhanced grazing is at odds to the current perspective that viral infections facilitates microbial mediated processes by diverting host material away from the higher trophic levels.

Effect of carrying a weighted backpack on lung mechanics during treadmill walking in healthy men - Paolo B. Dominelli; A. William Sheel; Glen E. Foster (European Journal of Applied Physiology, 2012)

Connectivity of Caribbean coral populations: complementary insights from empirical and modelled gene flow - NICOLA L. FOSTER; CLAIRE B. PARIS; JOHNATHAN T. KOOL; ILIANA B. BAUMS; JAMIE R. STEVENS; JUAN A. SANCHEZ; CAROLINA BASTIDAS; CLAUDIA AGUDELO; PHILLIPPE BUSH; OWEN DAY; RENATA FERRARI; PATRICIA GONZALEZ; et al. (Molecular Ecology, 2012)
Understanding patterns of connectivity among populations of marine organisms is essential for the development of realistic, spatially explicit models of population dynamics. Two approaches, empirical genetic patterns and oceanographic dispersal modelling, have been used to estimate levels of evolutionary connectivity among marine populations but rarely have their potentially complementary insights been combined. Here, a spatially realistic Lagrangian model of larval dispersal and a theoretical genetic model are integrated with the most extensive study of gene flow in a Caribbean marine organism. The 871 genets collected from 26 sites spread over the wider Caribbean subsampled 45.8% of the 1900 potential unique genets in the model. At a coarse scale, significant consensus between modelled estimates of genetic structure and empirical genetic data for populations of the reef‐building coral Montastraea annularis is observed. However, modelled and empirical data differ in their estimates of connectivity among northern Mesoamerican reefs indicating that processes other than dispersal may dominate here. Further, the geographic location and porosity of the previously described east–west barrier to gene flow in the Caribbean is refined. A multi‐prong approach, integrating genetic data and spatially realistic models of larval dispersal and genetic projection, provides complementary insights into the processes underpinning population connectivity in marine invertebrates on evolutionary timescales.

A blended global snow product using visible, passive microwave and scatterometer satellite data - James L. Foster; Dorothy K. Hall; John B. Eylander; George A. Riggs; Son V. Nghiem; Marco Tedesco; Edward Kim; Paul M. Montesano; Richard E. J. Kelly; Kimberly A. Casey; Bhaskar Choudhury (International Journal of Remote Sensing, 2011)

CYP2C19-guided design of a proton pump inhibitor dose regimen to avoid the need for pharmacogenetic individualisation in H. pylori eradication - Michael B. Ward; David J. R. Foster (European Journal of Clinical Pharmacology, 2011)

The synthetic triterpenoid CDDO-Imidazolide suppresses experimental liver metastasis - Jason L. Townson; Ian C. MacDonald; Karen T. Liby; Lisa Mackenzie; David W. Dales; Benjamin D. Hedley; Paula J. Foster; Michael B. Sporn; Ann F. Chambers (Clinical & Experimental Metastasis, 2011)

Nature of the Weipa Bauxite deposit, northern Australia - G. Taylor; R. A. Eggleton; L. D. Foster; D. B. Tilley; M. Le Gleuher; C. M. Morgan (Australian Journal of Earth Sciences, 2008)

Regolith profile, mineralogy and geochemistry of the Weipa Bauxite, northern Australia - R. A. Eggleton; G. Taylor; M. Le Gleuher; L. D. Foster; D. B. Tilley; C. M. Morgan (Australian Journal of Earth Sciences, 2008)

Using Blood Plasma for Monitoring Organochlorine Contaminants in Juvenile White Sturgeon, Acipenser transmontanus, from the Lower Columbia River - D. T. Gundersen; M. A. H. Webb; A. K. Fink; L. R. Kushner; G. W. Feist; M. S. Fitzpatrick; E. P. Foster; C. B. Schreck (Bulletin of Environmental Contamination and Toxicology, 2008)

Development of SHRIMP - T. R. Ireland*; S. Clement; W. Compston; J. J. Foster; P. Holden; B. Jenkins; P. Lanc; N. Schram; I. S. Williams (Australian Journal of Earth Sciences, 2008)

Changes in fire regimes since the Last Glacial Maximum: an assessment based on a global synthesis and analysis of charcoal data - M. J. Power; J. Marlon; N. Ortiz; P. J. Bartlein; S. P. Harrison; F. E. Mayle; A. Ballouche; R. H. W. Bradshaw; C. Carcaillet; C. Cordova; S. Mooney; P. I. Moreno; et al. (Climate Dynamics, 2008)

Pycnoporus cinnabarinus is pathogenic on living Paulownia trees - K. L. Bayliss; C. Foster; B. Dell; G. E. St. J. Hardy (Australasian Plant Pathology, 2007)

Incorporation of Plant Residues into Soil Organic Matter Fractions With Grassland Management Practices in the North American Midwest - S. A. Billings; C. M. Brewer; B. L. Foster (Ecosystems, 2006)

Mercury Concentrations in Gonad, Liver, and Muscle of White Sturgeon Acipenser transmontanus in the Lower Columbia River - M. A. H. Webb; G. W. Feist; M. S. Fitzpatrick; E. P. Foster; C. B. Schreck; M. Plumlee; C. Wong; D. T. Gundersen (Archives of Environmental Contamination and Toxicology, 2006)

Increased extracellular glutamate evoked by 1-Methyl-4-phenylpyridinium (MPP+) in the rat striatum is not essential for dopaminergic neurotoxicity and is not derived from released glutathione - Steven B. Foster; Haiwang Tang; Kenneth E. Miller; Glenn Dryhurst (Neurotoxicity Research, 2005)

Carbon monoxide levels at a toll plaza near Durban, South Africa - R. D. Diab; S. J. Foster; K. François; B. S. Martincigh; L. F. Salter (Environmental Chemistry Letters, 2005)

Loss of Linkage Disequilibrium and Accelerated Protein Divergence in Duplicated Cytomegalovirus Chemokine Genes - Ravit Arav-Boger; Jian-Chao Zong; Charles B. Foster (Virus Genes, 2005)

Identification Of Sex Pheromone Components Of The Painted Apple Moth: A Tussock Moth With A Thermally Labile Pheromone Component - A. M. El-Sayed; A. R. Gibb; D. M. Suckling; B. Bunn; S. Fielder; D. Comeskey; L. A. Manning; S. P. Foster; B. D. Morris; T. ando; K. Mori (Journal of Chemical Ecology, 2005)

The illusion of preservation: a global environmental argument for the local production of natural resources - Mary M. Berlik; David B. Kittredge; David R. Foster (Journal of Biogeography, 2002)
Aim The United States (US) and other affluent countries consume vast quantities of global natural resources, but contribute proportionately less to the extraction of many raw materials. This imbalance is due, in part, to domestic policies intended to protect the environment. Ironically, developed nations are often better equipped to extract resources in an environmentally prudent manner than the major suppliers. Thus, although citizens of affluent countries may imagine that preservationist domestic policies are conserving resources and protecting nature, heavy consumption rates necessitate resource extraction elsewhere and oftentimes under weak environmental oversight. A major consequence of this ‘illusion of natural resource preservation’ is greater global environmental degradation than would arise if consumption were reduced and a large portion of production was shared by affluent countries. This paper considers some implications of the consumption, management and conservation of forests and wood at a local and global scale. Location We focus on Massachusetts, the eighth most forested state in the USA (by area), the third most densely populated, and an affluent region with consumption rates that are among the highest in the country. Methods Estimates of wood production and consumption are generated, and comparisons are made with other commonly used materials (e.g. steel, concrete, aluminium). Results A comparison of the feasibility and environmental impact of various strategies for dealing with rising wood demand suggests that the US should strive to: (1) reduce per capita consumption of wood and its substitutes, (2) recycle forest products more effectively, (3) protect extensive areas of intensively managed and unmanaged forests and (4) promote sound forest management where the environmental consequences are mild. Forestry and the sustainable generation of wood in Massachusetts would allow preservation of primary forests elsewhere in the world. Main conclusions When aggressive reductions in wood consumption and effective recycling are combined with judiciously increased harvest levels, 50% of the Massachusetts's wood consumption could be met at sustainable rates, even while preserving large undisturbed blocks of forest.

A constitutive gene expression system derived from the tCUP cryptic promoter elements - K. Malik; K. Wu; X.-Q. Li; T. Martin-Heller; M. Hu; E. Foster; L. Tian; C. Wang; K. Ward; M. Jordan; D. Brown; S. Gleddie; et al. (Theoretical and Applied Genetics, 2002)

Bioaccumulation of PCBs in Aquatic Biota from a Tidal Freshwater Marsh Ecosystem - B. S. Crimmins; P. Doelling Brown; D. P. Kelso; G. D. Foster (Archives of Environmental Contamination and Toxicology, 2002)

Synoptic assessment of wetland function: a planning tool for protection of wetland species biodiversity - E. William Schweiger; Scott G. Leibowitz; Jeffrey B. Hyman; Walt E. Foster; Marla C. Downing (Biodiversity and Conservation, 2002)

Gonad Organochlorine Concentrations and Plasma Steroid Levels in White Sturgeon ( Acipenser transmontanus ) from the Columbia River, USA - E. P. Foster; M. S. Fitzpatrick; G. W. Feist; C. B. Schreck; J. Yates (Bulletin of Environmental Contamination and Toxicology, 2001)

Enhancers and core promoter elements are essential for the activity of a cryptic gene activation sequence from tobacco, tCUP - K. Wu; K. Malik; L. Tian; M. Hu; T. Martin; E. Foster; D. Brown; B. Miki (Molecular Genetics and Genomics, 2001)

Tetrodotoxin suppresses morphological enhancement of the metastatic MAT-LyLu rat prostate cancer cell line - S. P. Fraser; Y. Ding; A. Liu; C. S. Foster; M. B. A. Djamgoz (Cell and Tissue Research, 1999)

Turbulence and Coherent Organizations in the Atmospheric Boundary Layer: A Radar-Aircraft Experimental Approach - F. Lohou; B. Campistron; A. Druilhet; P. Foster; J.P. Pages (Boundary-Layer Meteorology, 1998)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)

Riparian Refugia in Agroforestry Systems - Mary Ellen Dix; Erol Akkuzu; Ned B. Klopfenstein; Jianwei Zhang; Mee-Sook Kim; John E. Foster (Journal of Forestry, 1997)

An immunocytochemical study of encephalic photoreceptors in three species of lamprey - J. M. García-Fernández; A. J. Jiménez; B. González; M. A. Pombal; R. G. Foster (Cell and Tissue Research, 1997)

Sectional notes - C. L. Fitch; E. L. Newdick; Frank W. Hussey; Ralph W. Donaldson; J. R. Livermore; E. B. Lyman; Robert Schmidt; E. J. Taintor; E. B. Tussing; J. B. R. Dickey; K. W. Lauer; G. S. Ralston; et al. (American Journal of Potato Research, 1934)